Riata lead failure manifests as electrical storm with lead parameters showing unique postural variations: a case report. Issue 12 (7th December 2021) - Uppal, Abhimanyu; Kathuria, Sanjeev; Shah, Bhushan; Trehan, Vijay
Abstract: Background: Riata implantable cardioverter-defibrillator (ICD) leads are prone to a unique type of mechanical lead failure causing conductor externalization (CE) which may be complicated by a delayed-onset electrical lead failure (ELF). Case summary: A 60-year-old male with symptomatic, severe ischaemic cardiomyopathy, and atrial fibrillation following a prior anterior wall myocardial infarction received a dual-chamber ICD with 7F-RiataST ventricular lead as a primary prevention strategy against sudden cardiac death in 2008. In 2017, a pulse generator replacement was performed for elective replacement indicator status. At that time, CE was noted in the ventricular lead but the electrical lead parameters were normal, hence lead replacement was decided against and the patient was closely followed up thereafter. Four years later, the patient presented with multiple ICD shocks within 48 h. Implantable cardioverter-defibrillator interrogation showed noise on the ventricular electrogram (EGM) channel that was detected as ventricular fibrillation (VF) episodes, triggering inappropriate ICD therapy (five ICD detected VF events within 24 h triggering three antitachycardia pacing therapies and one shock). Lead impedance and R-wave amplitude were within normal range in supine position but dramatically worsened in sitting posture. A new ventricular lead was implanted and the old lead abandoned. The patient has not experienced any device therapy in the follow-up period. Discussion: An electrically inert CE of Riata ICD leads needs close follow-up because an ELF may occur even after several years. A careful analysis of EGMs including postural changes in lead parameters can aid in detection and better characterization of underlying electrical dysfunction following CE.